PEMBERIAN ZAT PENGATUR TUMBUH SITOKININ TERHADAP VIGOR BIBIT KAKAO (Theobroma cacao L.) - Andri, Andri; Adelina, Enny; Adrianton, Adrianton (AGROTEKBIS, 2019)
This study aims to obtain a good concentration on the regeneration of growth regulators contained in coconut water on cocoa seed vigor (Theobroma cacao L). This research conducted at the Laboratory of Seed Science and Technology of Agriculture Faculty of Tadulako University. The experiment conducted from March to May 2017. This experiment used Complete Randomized Design, that are coconut water consisting of three levels = 50% of coconut water, = 75% of coconut water, = 100 % of coconut water. The treatments were repeated 10 times, so there are 30 units of treatments, each unit used 3 plants, so the number of plants observed is 90 plants. The results showed that the application of 100% of coconut water in cocoa seedlings were able to give better coconut seed vigor on increasing in plant height, increasing of leaf number, increasing of stem diameter, and total chlorophyll leaf compared to 75% concentration of coconut water and concentration 50% coconut water